2014
DOI: 10.1037/a0036797
|View full text |Cite
|
Sign up to set email alerts
|

The role of the verb in grammatical function assignment in English and Korean.

Abstract: One of the central questions in speech production is how speakers decide which entity to assign to which grammatical function. According to the lexical hypothesis (e.g., Bock & Levelt, 1994), verbs play a key role in this process (e.g., "send" and "receive" result in different entities being assigned to the subject position). In contrast, according to the structural hypothesis (e.g., Bock, Irwin, & Davidson, 2004), grammatical functions can be assigned based on a speaker's conceptual representation of an event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 59 publications
4
41
0
Order By: Relevance
“…These results are consistent with the claim that structural priming paradigms facilitate the structural mode of sentence planning (Van de Velde et al, 2014). Subsequent eye movements before speech onset, in the PreN1 region, indicated encoding of N1 (i.e., the Agent in active sentence trials; the Theme in passive sentence trials), whereas eye movements after speech onset (N1 and V regions) indicated encoding of N2 (i.e., the Theme in actives and the Agent in passives), consistent with previous studies on normal language production (Griffin and Bock, 2000; Gleitman et al, 2007; Hwang and Kaiser, 2014; Konopka and Meyer, 2014; Van de Velde et al, 2014). The unimpaired speakers in the present study ( M = 58 years) were slightly older than the participants with aphasia ( M = 48 years).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results are consistent with the claim that structural priming paradigms facilitate the structural mode of sentence planning (Van de Velde et al, 2014). Subsequent eye movements before speech onset, in the PreN1 region, indicated encoding of N1 (i.e., the Agent in active sentence trials; the Theme in passive sentence trials), whereas eye movements after speech onset (N1 and V regions) indicated encoding of N2 (i.e., the Theme in actives and the Agent in passives), consistent with previous studies on normal language production (Griffin and Bock, 2000; Gleitman et al, 2007; Hwang and Kaiser, 2014; Konopka and Meyer, 2014; Van de Velde et al, 2014). The unimpaired speakers in the present study ( M = 58 years) were slightly older than the participants with aphasia ( M = 48 years).…”
Section: Discussionsupporting
confidence: 88%
“…For example, studies have recorded eye movements while participants produce sentences describing two-character (Agent, Theme) scenes (e.g., a mailman chasing a dog) (Griffin and Bock, 2000; Gleitman et al, 2007; Cho and Thompson, 2010; Kuchinsky and Bock, 2010; Hwang and Kaiser, 2014; Konopka and Meyer, 2014; Van de Velde et al, 2014). Other studies have monitored eye movements as participants construct sentences with arrays of words (Lee and Thompson, 2011a,b).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to case marking and greater word-order flexibility, Japanese and Korean both have a Subject-Object-Verb (SOV) main clause basic word order in contrast to English's SVO order, and this word order difference itself may contribute to different planning constraints and demands. Recent work suggests that incremental sentence planning may proceed differently in verb-final languages, when the verb is uttered at the end (SOV word order), rather than in active sentences with SVO order (Hwang & Kaiser, 2014;Momma, Slevc & Phillips, 2016). Although the basic word order in Japanese and Korean may be SOV, these languages also have an alternative scrambled main clause word order in which the object precedes the subject in an OSV order.…”
mentioning
confidence: 99%
“…That is, it should not be possible to start preparing a sentence before the action is known since it is what ties the different participants in an event together and what will ultimately, in the form of a verb, underpin the relationships between the different sentence constituents. In fact, early psycholinguistic accounts of sentence production assumed verbs played a critical role in the generation of a sentence by being responsible for its basic structural shape (Levelt, 1989;Bock and Levelt, 1994;Ferreira, 2000)-an assumption that has found some empirical support from, among others, eye tracking and priming experiments (Pickering and Branigan, 1998;Melinger and Dobel, 2005;Hwang and Kaiser, 2014;Antón-Méndez, 2017;Sauppe, 2017). For example, Antón-Méndez (2017, Figure 3) found facilitation during picture description when the action in the sentence to be produced had been linguistically primed, but not when the subject had been visually primed, suggesting the verb plays a major role in sentence planning.…”
Section: Introductionmentioning
confidence: 99%